STUDENTS’ AND ENGLISH TEACHERS’ PERCEPTION TOWARD THE IMPLEMENTATION OF MERDEKA BELAJAR CURRICULUM AT 10th GRADE OF SMK NEGERI 1 MAJENE - Nurlailah, Nurlailah; Syamsinar, Syamsinar; Adawiah, Rabiatul (Borneo Journal of English Language Education, 2024)
The research problem for this research is how students’ and English teachers’ perception toward the implementation of Merdeka Belajar curriculum. The purpose of this research is to determine the perception of students and English teachers towards the implementation of Merdeka Belajar among vocational high school. The researchers used mixed method to collect data using a questionnaire and interview instrument. The sample of this research were the students of class 10th consist of 30 students and two English teachers of SMK Negeri 1 Majene. The result showed that students’ perception toward the Merdeka Belajar was in the undicedid category with a total of 64.80% and English teachers’ perception toward the implementation of Merdeka Belajar was in the agree category with a total of 79.17%. This indicates that students’ perceptions of Merdeka Belajar are undicedid, while English teachers’ perceptions of Merdeka Belajar are agree. Keywords: Perception, Merdeka Belajar Curriculum